Uncovering the Tradeoffs and Synergies of Ecosystem Services in Mining Landscapes: Spatiotemporal and Factor Detection Perspective - Jiao Pan; Tao Chen; Antonio Plaza (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Revealing the spatial-temporal evolution and interactions of ecosystem services (ESs) in mining area is critical for sustainable environmental management. The temporal and spatial characteristics and changing trends of six ESs in Yuzhong mining area from 2000 to 2020 were analyzed. Pearson correlation analysis explored and elucidated the intricate tradeoffs and synergies that manifest across diverse ecosystems. The integrated ecosystem service landscape index (IESLI) was constructed on this basis, and 8 factors (both natural and human) were selected to identify the driving forces. The findings indicated that: 1) Over the past two decades, five categories of ESs have exhibited a declining trend, with water yield experiencing the most significant reduction, reaching 38.7% . 2) Among the 15 ESs pairings, tradeoffs were predominantly negatively correlated. 3) The interaction between land use/land cover and precipitation (54.5% ) emerged as the primary driving force behind the spatial heterogeneity of ESs. 4) The IESLI showed a general downward trend, decreasing from 0.51 in 2005 to 0.44 in 2020. This study provides quantitative evidence of ecosystem degradation and the intricate interrelationships among ESs in mining landscapes, highlighting the critical role of coupled spatial models in uncovering underlying patterns and mechanisms. The findings offer a scientific foundation for ecological restoration and policy-making in mining regions.